Effectiveness of Interval Training Using Maximum Aerobic Speed (MAS) to Improve Aerobic Capacity - Indah Nurwulan; Dikdik Zafar Sidik; Fitri Rosdiana (Journal of Physical Education Health and Sport, 2025)
This study aimed to investigate the impact of personalized interval training (short and long) based on Maximum Aerobic Rate (MAS) on improving athletes’ aerobic capacity. Using quantitative experimental method with 2x2 factorial design, 16 athletes were divided into four groups: SIT-MAS High, SIT-MAS Low, LIT-MAS High, and LIT-MAS Low. Although the Friedman test showed no statistically significant differences in aerobic improvements among the four groups overall, intra-group analysis showed mixed results. Statistically significant increases in aerobic capacity were found in the  LIT-MAS High and SIT-MAS low groups, which supported the third and fifth hypotheses. In contrast, the improvements in the SIT-MAS High and LIT-MAS Low groups were not significant. There was also a significant difference between SIT and LIT in the low MAS group, but not in the high MAS group. This study concludes that personalization of interval training based on an individual’s MAS profile is important, with LIT shown to be effective for low MAS athletes and SIT effective for high MAS athletes. Limitations of this study include the very small sample size (n=3 or n=4 per group), as well as external factors such as inconsistent training schedules, pressure from competition, and athlete injuries.